Descriptions of two new species of American Cerambycidae, and redescription of Leptostylus subfurcatus (Cerambycidae, Coleoptera) - Heffern, Daniel; Santos-Silva, Antonio (Zootaxa, 2023)
Two new species are described: Aneflus (Aneflus) monzoni sp. nov. (Cerambycinae, Elaphidiini), from Guatemala; and Aegomorphus personatus sp. nov. (Lamiinae, Acanthoderini), from Mexico. Leptostylus subfurcatus Bates, 1880 is redescribed based on a female from Panama, and a variation of the outer apex of the metafemora is reported for the first time.